Perspectives on Maimonides : philosophical and historical studies - Kraemer, Joel L.; Berman, Lawrence V. (Lawrence Victor); Blau, Joshua, 1919-2020. (London ; Portland, Or. : Littman Library of Jewish Civilization, 2008)
This is a text on the philosophy and legal views of Moses Maimonides (1138-1204) and the historical context in which he worked. The philosophical section examines Maimonides' ethical doctrine; his paradoxical life-style; his 'Guide of the Perplexed'; his attitude to mysticism; his use of language; and his theory of astronomy. The legal section deals with law and medicine, the relation of Maimonides' legal thought to the Talmud; his doctrine of a just war; and his theory of redemption and Messianism. The history section examines Maimonides' accession to the position of head of the Jewish community in its historical context, at the time of the rise of the Ayyubid dynasty under Saladin.
The ethical view of Maimonides within the context of Islamicate civilization / Lawrence V. Berman -- Maimonides' governance of the solitary / Ralph Lerner -- Maimonides in the Sultan's Palace / Steven Harvey -- Maimonides on the philosophic sciences in his Treatise on the Art of Logic / Joel L. Kraemer -- Why Maimonides was not a Mutakallim / Warren Zev Harvey -- Neoplatonic currents in Maimonides' thought / Alfred L. Ivry -- Maimonides' quest beyond philosophy and prophecy / Ithamar Gruenwald -- The 'true perplexity' : the Guide of the Perplexed, Part II, Chapter 24 / Tzvi Langermann -- Maimonides on religious language / Arthur Hyman -- Maimonides' Guide of the Perplexed on forbidden food in the light of his own medical opinion / Jacob Levinger -- Holy War in Maimonidean law / Gerald J. Bilstein -- 'To the utmost of human capacity' : Maimonides on the days of the Messiah / Aviezer Ravitzky -- Maimonides on Eretz, Yisrael : halakhic, philosophic, and historical perspectives / Isadore Twersky -- 'At our place in al-Andalus', 'At our place in the Maghreb' / Joshua Blau -- The early decades of Ayyūbid rule / Joseph Drory -- Saladin's Egypt and Maimonides / Andrew S. Ehrenkreutz -- Saladin's religious personality, policy, and image / Michael Winter.
"This volume is the proceedings of a colloquium held at Tel Aviv University in June 1982 under the auspices of the Kaplan chair."
Contributors: Joel L. Kraemer, Lawrence V. Berman, Joshua Blau."--Back cover
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Maimonides, Moses, -- 1135-1204 -- Congresses; Maimonides, Moses, -- 1135-1204; Jewish philosophy -- Congresses; Philosophy, Medieval -- Congresses; Philosophie juive -- Congrès.; Philosophie médiévale -- Congrès.; Jewish philosophy; Philosophy, Medieval; Conference papers and proceedings